Design, fabrication, and testing of an electronic device for the automatic control of electrochromic windows. (July 2017) - Papathanasopoulos, D.; Leftheriotis, G.; Mitronikas, E.
Abstract: In this study, an electronic apparatus for transmittance control of electrochromic windows is presented. The system is based on a microcontroller that, combined with a suitable interface, allows the user to choose among different operating modes. In addition, either voltage or current control can be performed, counting six different modes in total. Silicon photodiodes are used for sensing both the incident radiation and the transmittance of the window. Furthermore, the electronic device can be re-programmed to perform different tasks, providing a versatile tool for real time testing of electrochromics in outdoor conditions. The proposed controller can be combined with different electrochromic devices, regardless of their fabrication method or size. To test the controller, an electrochromic prototype 10 cm by 10 cm was used as a load. The experimental set-up has been tested in real time outdoor conditions and the system stability was verified, regardless of fluctuations of the incident radiation, partial shading of the system and ion diffusion effects. For the electrochromic window tested, a transmittance change from 60% to 10% or vice versa lasts approximately 210 s with voltage control, while the same operation lasts 600 s with current control, as in that case, the applied current is limited to 2.5 mA. Highlights: The robustness of the system was verified under real time outdoor conditions. Protective functions were implemented to extend the lifespan of the window. The transmittance sensing was more reliable when uncoupled from solar radiation. Constant voltage control outperformed the constant current one in terms of speed. Constant current control was less stressful to the window.